Study on shear-thickening-assisted abrasive lapping and polishing of SiC ceramic substrate: parameter optimization and surface quality evaluation - Pan, Fangwei; Yuan, Haiyang; Shi, Hongwei; Fang, Zheng; Huang, Yibo; Lin, Youbin; Wu, Jixuan (Frontiers in Materials, 2025)
This study investigates the rheological properties of shear-thickening polishing fluids with varying compositions using rheometric analysis. The results reveal a significant correlation between the fluid’s rheological behavior and the mass fraction of the dispersant phase, identifying an optimal mass fraction of 40 wt%. Further experiments, conducted using a customized metallographic grinding machine, systematically analyze the influence of key process parameters. The investigation demonstrates that a lapping duration of 30 min and a polishing duration of 45 min yield optimal performance. Additionally, external pressure experiments indicate that both material removal rate and surface roughness increase with applied pressure, reaching a plateau due to reduced fluid flow and enhanced abrasive penetration, with an optimal pressure of 150 kPa. Furthermore, experiments with varying abrasive particle sizes show that material removal rate and surface roughness increase with larger particles, with an optimal size of 3 μm. In summary, this study establishes the optimal parameters for the integrated shear-thickening assisted abrasive lapping and polishing process: an abrasive particle size of 3 μm, a polishing pressure of 150 kPa, a lapping time of 30 min at 200 rpm, and a polishing time of 45 min at 100 rpm. The implementation of these optimized parameters achieves a surface roughness of 9.7 nm on SiC ceramic substrates, demonstrating the effectiveness of this advanced processing technique.